Students' Computer Literacy Skill, Motivation, and Reading Comprehension in Eleventh Grade - Budiyanto, Darmawan; Tridinanti, Gaya; Ridho, M.Rasyid (Universitas Pendidikan Ganesha, 2024)
Computer literacy, defined as the ability to effectively use computers and related technologies, is increasingly important in modern education. This study aims to analyze the relationships between computer literacy, student motivation, and reading comprehension among eleventh-grade students. A correlational research design was used, involving 300 students selected through stratified random sampling. Data collection was based on the International Computer and Information Literacy Study (ICILS) for assessing computer literacy, the Academic Motivation Scale (AMS) for measuring motivation, and the Gates-MacGinitie Reading Tests (GMRT) for evaluating reading comprehension. Statistical analyses, including Pearson correlation and multiple regression, were performed using SPSS software. Results showed significant positive correlations among computer literacy, motivation (both intrinsic and extrinsic), and reading comprehension. Computer literacy had a strong correlation with reading comprehension (r = 0.60, p < 0.01). Intrinsic motivation (r = 0.62, p < 0.01) and extrinsic motivation (r = 0.48, p < 0.01) also positively correlated with reading comprehension. Multiple regression analysis indicated that computer literacy (β = 0.42, p < 0.001) and intrinsic motivation (β = 0.38, p < 0.001) were significant predictors of reading comprehension, with extrinsic motivation contributing as well (β = 0.22, p < 0.01). The novelty of this research lies in its integrated examination of computer literacy, motivation, and reading comprehension. The findings underscore the importance of these factors in enhancing academic achievement.